Missing disinflation and missing inflation: the puzzles that aren't - Elena Bobeica; Marek Jarociński (European Central Bank (ECB), 2017)
In the immediate wake of the Great Recession we didn't see the disinflation that most models predicted and, subsequently, we didn't see the inflation they predicted. We show that these puzzles disappear in a Vector Autoregressive model that properly accounts for domestic and global factors. Such a model reveals, among others, that domestic factors explain much of the inflation dynamics in the 2012-2014 euro area missing inflation episode. Consequently, economists and models that excessively focused on the global nature of inflation were liable to miss the contribution of deflationary domestic shocks during this episode.
Keywords: E31; E32; F44; 330; Bayesian vector autoregression; conditional forecast; inflation dynamics; international transmission of shocks; Phillips curve; shock identification